Dam construction alters planktonic microbial predator‒prey communities in the urban reaches of the Yangtze River. (15th February 2023) - Wang, Qiaojuan; Chen, Junwen; Qi, Weixiao; Wang, Donglin; Lin, Hui; Wu, Xinghua; Wang, Dianchang; Bai, Yaohui; Qu, Jiuhui
Highlights: Bacteroidetes and eukaryotic predators were enriched upstream of dam. Actinobacteria and phototrophic eukaryotes were enriched downstream. Predator-prey interactions were reduced downstream. The microbial community was more influenced by dam than by other variables. Dam induced detritus-based food webs switching to autotroph-based food webs. Abstract: While dam construction supports social and economic development, changes in hydraulic conditions can also affect natural aquatic ecosystems, especially microbial ecosystems. The compositional and functional traits of multi-trophic microbiota can be altered by dam construction, which may result in changes in aquatic predator–prey interactions. To understand this process, we performed a large-scale sampling campaign in the urban reaches of the dam-impacted Yangtze River (1 995 km) and obtained 211 metagenomic datasets and water quality data. We first compared the compositional traits of planktonic microbial communities upstream, downstream, and in a dam reservoir. Results showed that Bacteroidetes (R-strategy) bacteria were more likely to survive upstream, whilst the reservoir and downstream regions were more conducive to the survival of K-strategy bacteria such as Actinobacteria. Eukaryotic predators tended to be enriched upstream, whilst phototrophs tended to be enriched in the reservoir and downstream regions. Based on bipartite networks, we inferred that the potential microbial predator–prey interactions gradually and significantly decreased from upstream to the downstream and dam regions, affecting 56% of keystone microbial species. Remarkably, functional analysis showed that the abundance of the photosynthetic gene psbO was higher in the reservoir and downstream regions, whilst the abundance of the KEGG carbohydrate metabolic pathway was higher upstream. These results indicate that dam construction in the Yangtze River induced planktonic microbial ecosystem transformation from detritus-based food webs to autotroph-based food webs. Graphical abstract: Image, graphical abstract